Linearly π-conjugated oligothiophenes as simple metal-free sensitizers for dye-sensitized solar cells1. Issue 29 (7th August 2015) - Demeter, Dora; Roncali, Jean; Jungsuttiwong, Siriporn; Melchiorre, Fabio; Biagini, Paolo; Po, Riccardo
<x xml:space="preserve">Abstract</x> Oligothiophenes with a terminal acceptor anchoring group can act as simple and efficient metal-free sensitizers for DSSCs.